PRINCIPLES OF TEACHING ENGLISH TO PRIMARY SCHOOL LEARNERS THROUGH ART-BASED METHOD (SCIENCE TIME JOURNAL, 2026)
This article examines the didactic, psychological, and pedagogical principles of teaching English to primary school learners through visual and arts-based tools. Special attention is given to the role of pictures, graphic images, drama, and creative activities in developing young learners’ speech skills. The study systematizes general didactic, psycholinguistic, methodological, and pedagogicalprinciples relevant to primary foreign language education. Based on theoretical analysis of national and international research, a framework of principles for arts-integrated English language teaching is proposed. The findings indicate that visual support, communicative orientation, age-appropriate instruction, and multisensory engagement significantly enhance vocabulary acquisition, oral speech development, and learner motivation. The article contributes to the theoretical foundation of arts-based English language teaching in primary education.